Student perceptions of the use of VR to introduce Malang local tourism and culture - Muzaki, Helmi; Gatut Susanto; Kusubakti Andajani; Afiyahtun Isnaeni; Ilham Akhsani; Thilip Kumar Moorthy (Universitas Negeri Yogyakarta, 2025)
This study investigates students’ perceptions of the use of Virtual Reality (VR) as a learning medium for introducing tourism and local culture in Malang. This research employed a quantitative descriptive design involving 23 first-semester students selected through purposive sampling. Data were collected using a Likert-scale questionnaire (1–5) consisting of 17 statements that measured learning effectiveness, educational value, tourism introduction, cultural understanding, and the development of knowledge and skills. The results indicate that students demonstrated highly positive perceptions of VR implementation, with an overall mean score of 4.34. The highest score was obtained in the aspect of local tourism introduction (M = 4.46), followed by local cultural understanding (M = 4.41) and learning effectiveness (M = 4.37). These findings show that VR provides an immersive and engaging learning experience that enhances students’ understanding of tourism and local culture. Therefore, it is recommended that educators and institutions further integrate and develop VR as an innovative technology-based learning strategy to enrich educational practices.